The Realization of Conversational Implicatures in Listening Comprehension of ‘Longman Preparation Course for the TOEFL Test’ - Etik Khusnul Khotimah; Djanuarius Mujiyanto; Hendi Pratama (Universitas Negeri Semarang, 2022)
Studying implicatures cannot be separated from studying pragmatics. Studying pragmatics is studying meaning in context. Understanding meaning in context is very essential in communication. The purpose of the study was to explain the realization of idiosyncratic and formulaic conversational implicatures in listening comprehension section of ‘LONGMAN Preparation Course for the TOEFL Test’. Qualitative research is used to collect data, analyze the data, and take a conclusion based on the analysis of the findings. The type of qualitative study used is content analysis. In a TOEFL book titled LONGMAN Preparation Course for the TOEFL Test, data were implicatures in every conversation covered in the script of the short conversation of listening comprehension section. The researcher found that the four types of idiosyncratic implicature were all in the short conversations of listening comprehension section in the TOEFL book